2017
DOI: 10.1039/c7dt02180a
|View full text |Cite
|
Sign up to set email alerts
|

Hoveyda–Grubbs catalyst analogues bearing the derivatives of N-phenylpyrrol in the carbene ligand – structure, stability, activity and unique ruthenium–phenyl interactions

Abstract: We have synthesized a series of N-phenylpyrrole and N-phenylindole carbenes and used them as ruthenium-ligating moieties in the synthesis of Hoveyda-Grubbs catalyst derivatives. We show that most of these complexes are difficult to synthesize and unstable apart from the N-phenylpyrrole-2,6-diisopropylphenyl ruthenium complex and its perbrominated derivative. These two systems are almost completely inactive in ring-closing metathesis at room temperature and become active only at 80 °C. DFT, SAPT0 and DLPNO-CCSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 84 publications
1
18
0
Order By: Relevance
“…Recently, we developed a new class of uNHC ligands, bearing in addition to one "standard" N-aryl substituent (Mes, DIPP), a second arm containing a heterocyclic substituent such as thiophene, benzothiophene, furan, benzofuran, or pyrrole, flexibly connected to NHC via CH 2 group (Figure 5). [51][52] All corresponding indenylidene and Hoveyda-type ruthenium complexes (Ru47-52), [51] except these with pyrrole substituents (Ru53-54) [52] demonstrated a significant level of robustness toward air and moisture. The catalytic activity of these complexes was probed through a set of model RCM reactions.…”
Section: A Versatile Thiophene-based Unhc Ru Catalystmentioning
confidence: 99%
“…Recently, we developed a new class of uNHC ligands, bearing in addition to one "standard" N-aryl substituent (Mes, DIPP), a second arm containing a heterocyclic substituent such as thiophene, benzothiophene, furan, benzofuran, or pyrrole, flexibly connected to NHC via CH 2 group (Figure 5). [51][52] All corresponding indenylidene and Hoveyda-type ruthenium complexes (Ru47-52), [51] except these with pyrrole substituents (Ru53-54) [52] demonstrated a significant level of robustness toward air and moisture. The catalytic activity of these complexes was probed through a set of model RCM reactions.…”
Section: A Versatile Thiophene-based Unhc Ru Catalystmentioning
confidence: 99%
“…In our previous studies on benzyl‐substituted uNHC (e.g., L2 ), we found that an increase of the steric bulk of the N ‐aromatic substituent, by replacing Mes with DIPP, brought promising enhanced selectivity to the catalysts derived from such altered ligands, however at the cost of slightly diminished activity ,. In the present work, we decided to focus on the not yet fully explored class of uNHC ligands that bear a heterocyclic N ‐substituent in their structure ,,. We opted to check if modification of the thiophene‐based uNHC ligand can lead to a catalyst of higher selectivity, which is at the same time easy to handle, tolerant to diverse functional groups, and sufficiently active to be applied in more polar (green) solvents.…”
Section: Introductionmentioning
confidence: 99%
“…This is even more surprising given the fact that there are hundreds of known NHCs and a large number of studies on how the structural changes in carbenes affect the catalytic activities of ruthenium olefin metathesis catalysts. 3 , 7 , 8 , 35 38 In this work, we show how small changes in NHC side groups affect the Gibbs free energy barriers for tandem hydrogenation/C–H activation of derivatives of 1 ( Figure 3 ) as well as take a closer look at the rate-limiting steps for this type of reaction. To perform this task, we performed computational studies on the catalytic pathway for five different catalysts including 1 and four similar systems with structural changes in the carbene part, based on crystal structures of known NHCs, commonly used in various Ru catalysts ( 3 – 5 , Figure 3 ).…”
Section: Introductionmentioning
confidence: 88%